P418 Development and validation of a digital health platform (IBD NutriCare) for telenutrition in patients with Inflammatory bowel disease. (21st January 2022) - Gupta, A; Singh, N; Madan, D; Farooqui, M; Singh, N; Singh, M; Virmani, S; Verma, M; Bajaj, A; Markandey, M; Kante, B; Vuyyuru, S K; et al.
Abstract: Background: Introduction -Telenutrition with digital health platforms is the future step towards improving patient care in patients with inflammatory bowel disease(IBD). Additionally, it offers an advantage of conducting multicenter longitudinal dietary intervention studies. Aim -To develop and validate a digital health platform for patients with IBD to provide nutrition care and record longitudinal diet data on a large-scale basis. Methods: Methods -The development of the digital health platform was done from October, 2019 -June, 2021 by gastroenterologists and dieticians. For validation, patients with IBD at All India Institute of Medical Sciences, New Delhi recorded, 7 days diet in the App. 24-hours diet recall for, 3 days at random during the same week was also done. Energy, protein, carbohydrate, fat, fiber, cereals, fruits, vegetables, grain, legumes, milk products were compared between two methods. Results: Results -An Android and iOS-based digital health platform, 'IBDNutriCare' was developed in English and, 7 Indian languages. This user-friendly interface can be downloaded by the patients free of cost from Google store and App store. This platform provides a recording of diet variables based on, 600 Indian food recipes, patient parameters like subjective global assessment, medications, and clinical activity scores. It also provides a graphical representation of nutrient analysis, with web applications generating comprehensive reports to enable large-scale data analysis. Forty-nine patients with IBD were enrolled in a validation study comparing 'IBDNutricare' based analysis with dietary recall method. The mean intake of all food groups and macronutrients was comparable between the two methods. There was a significant interclass correlation [excellent for macronutrients and all food groups except vegetables (moderate, 0.79] and Bland-Altman plot analysis showed good agreement between the two methods. Conclusion: Conclusion- This study developed and validated a digital health platform for telenutrition in patients with IBD. This app helps in real-time tracking of dietary details and recording the data on a large scale.